Effectiveness of interventions for optimising adherence to treatments for the prevention and management of scars: A systematic review. (May 2021) - Killey, Jessica; Simons, Megan; Tyack, Zephanie
Objectives: To identify the adherence interventions used with people receiving treatments to prevent or manage scarring, the effectiveness of these interventions, and the theoretical frameworks on which these interventions were based. Data sources: Databases (PubMed, Embase, Web of Science, CINAHL, PsychINFO and OTseeker) were searched (09.10.2020) with no date or language restrictions. Grey literature databases, clinical trial registries and references lists of key papers were also searched. Review methods: Eligible randomised controlled trials included people using treatments for scarring following skin wounds, interventions that may improve adherence, and outcomes measuring adherence. Risk of bias (selection, performance, detection, attrition, reporting) and certainty of evidence (inconsistency, imprecision, indirectness, publication bias) were assessed. Results: Four randomised trials were included with 224 participants (17 children) with burn scars. Interventions involved educational (three trials) or technology-based components (four trials) and ranged in length from two weeks to six months. All four trials reported greater adherence rates in the intervention group compared with standard practice [standardised mean difference = 1.50 (95% confidence interval (CI) = 0.91–2.08); 2.01 (95% CI 1.05–2.98); odds ratio = 0.28 (95% CI = 0.11–0.69)]. One trial did not report original data. The certainty of evidence was very low. Conclusion: Adherence interventions using education or technology for people receiving burn scar treatment may improve adherence. Further studies are needed particularly in children, with a focus on including outcomes of importance to patients (e.g. quality of life) and identifying core components of effective adherence interventions using theoretical frameworks.